Quality of life in temporomandibular disorder patients with localized and widespread pain - Maísa Soares Gui; Marcele Jardim Pimentel; Marta Cristina da Silva Gama; Glaucia Maria Bovi Ambrosano; Célia Marisa Rizzatti Barbosa (Universidade Estadual de Campinas, 2010)
Aim: To compare temporomandibular (TMD) subgroups classified according to the presence of localized pain (LP) or widespread pain (WP) in order to assess the quality of life domains and verify which components affect most the functional capacity of facial pain patients. Methods: A cross-sectional study was conducted and the Short Form-36 Health Survey was applied in order to assess quality of life. Thirty-nine TMD/WP patients, 37 TMD/LP patients and 40 subjects free of TMD complaints were evaluated. Results: TMD/WP patients differed significantly from healthy controls in all SF-36 components and TMD/LP patients ranked between them. It was also observed that patients with bodily pain and TMD with WP are respectively, 4.16 and 49.42 times more likely to have low functional capacity. Conclusions: Functional capacity in TMD subgroups was only affected by the presence of bodily pain and WP. These patients feature high chance of low functional capacity. Furthermore, TMD patients with localized and widespread pain share roleemotional impairments.